Digital Generation: Teaching Methods and Technologies during Pandemic - T. I. Zakharova (Вестник Российского экономического университета имени Г. В. Плеханова)
The need in high-quality education has always been and now is acute for learners and their parents all over the world. Only the most advanced methods, methodology and practices can enable teachers to cover completely the subject field and develop skills of analytical and critical thinking of the digital generation or generation Z, as we call people born after 2000. The situation formed by COVID-19 pandemic changes traditional foundations of life, business, education in the world. In March 2020 the majority of educational institutions were forced to change to distance learning. A lot of conventional forms of teaching underwent serious changes. Not only the process of teaching was altered, but the system of teacher – learner interaction was modified. Pandemic and restrictions imposed by it differ from country to country. Special attention is paid to distance forms using multimedia technologies. Today digital projects of distance learning integrated in the classic system of education are being developed. The author showed that difficulties arising with teaching high-school learners and university students point to the necessity to focus teachers’ attention on digital generation.